Digitalisation in hospitals in COVID-19 times: A case study of the Czech Republic - Jarmila Zimmermannova; Lukas Pavlik; Ekaterina Chytilova (Economies, 2022)
In COVID-19 times, the healthcare system needs more financial and other resources for covering all necessary medical products and services. On the other hand, we have observed pressure on the effectiveness and optimisation of resources in hospitals and healthcare facilities. Digitalisation represents an important source of information for various levels of management in hospitals. The main aim of our research is the identification of the benefits of digitalisation of medical devices in hospitals in COVID-19 times, focusing on a case study of the Czech Republic. For our methodological approach, a literature review, data analysis, correlation analysis, and regression analysis were used. The case study presents the changes to the equipment/facilities use in years 2019 and 2020 in a selected hospital in Prague and the impact of COVID-19 on such use of resources. Management and financial issues are discussed, together with recommendations for healthcare sector management. As a result, economic benefits are represented mainly by various kinds of savings and optimisation of both processes and employees. On the other hand, it is not easy to identify all possible savings, as some of them can be in non-financial expression.
Keywords: 330; digitalisation; hospital; optimisation of resources; equipment/facilities; COVID-19; benefits; savings